ANALISIS DAMPAK KARAKTERISTIK PEKERJAAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN SEBAGAI ISU SENTRAL DALAM DUNIA USAHA (Study Kasus pada PT. POS Indonesia (Persero) Pamekasan) - Syaiful Syaiful (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2018)
The research objective to be achieved from this research is to prove the influence of job characteristics and the development of human resources compensation on the motivation and performance of employees at PT. Pos Indonesia (Persero) Pamekasan. This research is quantitative research with survey approach population in this study were all employees of PT. Pos Indonesia (Persero) Pamekasan as many as 60 employees, the sample used is 60 people using census techniques. In this research analyzed using Partial Least Square (PLS). The results showed that: job characteristics and significant positive effect on employee motivation PT. Pos Indonesia (Persero) Pamekasan. It means that the better and the obvious characteristics of the work performed, the employees work motivation of employees of PT. POS Indonesia Persero Pamekasan will also be higher. Human resource development and significant positive effect on the motivation of employee PT. POS Indonesia Persero Pamekasan. It means that the better implementation of human resource development granted to employees of the motivation of employee PT. POS Indonesia Persero Pamekasan will also be higher. Characteristics Work has positive and significant impact on the performance of employees of PT. POS Indonesia Persero Pamekasan. It means that the better and the obvious characteristics of the work performed, the performance of employees of PT. POS Indonesia Persero Pamekasan will also be higher. Human Resources Development has a positive and significant impact on the performance of employees of PT. POS Indonesia Persero Pamekasan. It means that the better implementation of human resource development granted the performance of employees of PT. POS Indonesia Persero Pamekasan will also be higher. Compensation have a positive and significant impact on the performance of employees of PT. POS Indonesia Persero Pamekasan. It means that the higher compensation to employees, the performance of employees of PT. POS Indonesia Persero Pamekasan will also be higher. Work Motivation has a positive and significant impact on the performance of employees of PT. POS Indonesia Persero Pamekasan.